2006
DOI: 10.1196/annals.1317.043
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Stimulates the Release of Interleukin‐6 in Cultured Rat Müller Cells

Abstract: We have investigated the in vivo effect of PACAP on rat Müller cells that are the predominant glial element in the retina. Müller cells were treated with PACAP38, either alone or in the presence of the PACAP-selective antagonist, PACAP6-38. Cellular proliferation was determined by measuring the incorporation of bromodeoxyuridine, while interleukin-6 (IL-6) levels in the culture medium were examined using a B9 cell bioassay. In cultured rat Müller cells, the expression of PACAP receptor (PAC1-R) was assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…For instance, these cells in culture accumulate cyclic AMP induced by catecholamines (Kubrusly et al 2008), display GABA uptake properties (De Sampaio Schitine et al 2007) and PACAP-induced activation of adenylyl cyclase (Kubrusly et al 2005). They also express glutamic acid decarboxylase, beta 2 nicotine acetylcholine receptors, enzymes of catecholamine metabolism, including tyrosine hydroxylase (Kubrusly et al 2005(Kubrusly et al , 2008Seki et al 2006), glutamate (Ramirez and Lamas 2009), and muscarinic acetylcholine receptors (Wakakura et al 1998). Chick Müller cells in culture express several excitatory amino acids (EAAs) receptors that are coupled to inositol triphosphate mobilization and 45 Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…For instance, these cells in culture accumulate cyclic AMP induced by catecholamines (Kubrusly et al 2008), display GABA uptake properties (De Sampaio Schitine et al 2007) and PACAP-induced activation of adenylyl cyclase (Kubrusly et al 2005). They also express glutamic acid decarboxylase, beta 2 nicotine acetylcholine receptors, enzymes of catecholamine metabolism, including tyrosine hydroxylase (Kubrusly et al 2005(Kubrusly et al , 2008Seki et al 2006), glutamate (Ramirez and Lamas 2009), and muscarinic acetylcholine receptors (Wakakura et al 1998). Chick Müller cells in culture express several excitatory amino acids (EAAs) receptors that are coupled to inositol triphosphate mobilization and 45 Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have suggested that PACAP stimulates the production of interleukin-6 (IL-6), a proinflammatory cytokine, in rat astrocytes and muller cells as well as mouse calvarial osteoblasts (Tatsuno et al, 1996;Seki et al, 2006). IL-6 produced by osteoblasts/stromal cells has been demonstrated as a key factor for excessive bone resorption in physiological conditions such as postmenopausal osteoporosis (Suda et al, 1991;Pfeilschifter et al, 2002;, hyperparathyroidism (Grey et al, 1999) and Paget's disease (Roodman, 2001).…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
“…Infiltrating cells, retinal glial cells, and pigment epithelial cells are possible sources of IL-6, IL-1ß, TNFα, and interferon-γ in the vitreous of patients with PVR [18,[195][196][197][198][199][200][201]. Müller cells produce IL-6 [202,203], e.g. upon stimulation with IL-1ß and advanced glycation end products [204,205].…”
Section: Factors Involved In Müller Cell Gliosis and Proliferationmentioning
confidence: 99%